Proton and pion production in Au+Au collisions at 10.8A GeV/c - Barrette, Jean; Stachel, Johanna; Wessels, Johannes P. (Arxiv, 2000)
We present proton and pion tranverse momentum spectra and rapidity distributions for Au+Au collisions at 10.8A GeV/c. The proton spectra exhibit collective transverse flow effects. Evidence of the influence of the Coulomb interaction from the fireball is found in the pion transverse momentum spectra. The data are compared with the predictions of the RQMD event generator.
Gesehen am 27.02.2020